PENGGUNAAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT MATERI BARISAN DAN DERET KELAS XI SMK - Azukario, Azukario; Hamdani, Hamdani; Yani, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the effectiveness used of the teams games tournamenttype of cooperative learning model on arithmetic sequence and sequence material in the 11thgradeSMKN 1 Pontianak. The research method was experiment and the form of was pre-experimental design with one shot case study.30 students of 11th AK 4SMKN 1 Pontianak were taken as the research samples.Indicators used to determine the effectiveness of learning using the teams games tournament type of cooperative learning modelare : student?s learning activity, student?s learning outcomes, and student?s responses. Data collectiontechniques usedare documentation techniques, measurement techniques, observation techniques, and indirect communication techniques. The data collectiontoolsare,the student?s learning activity observation sheet, the student?s learning outcomes test and student?s responses questionnaire. The result of data analysis showed thatthe student?s learning activity isactive, student?s learning outcomes completeness achieved classically, and students provide apositive responses to learning.The effectiveness of used the teams games tournament  type of cooperative learning model on arithmetic sequence and sequence material in the 11th gradeSMKN 1 Pontianakis effective. Keyword: Arithmetic Sequence and Sequence Material,Cooperative Model,Teams Games Tournament